CdSe supported SnO2 nanocomposite with strongly hydrophilic surface for enhanced overall water splitting. (1st August 2022) - Nisa, Mehar Un; Manzoor, Sumaira; Abid, Abdul Ghafoor; Tamam, Nissren; Abdullah, Muhammad; Najam-Ul-Haq, Muhammad; Al-Buriahi, M.S.; Alrowaili, Z.A.; Mahmoud, Zakaria M.M.; Ashiq, Muhammad Naeem
Graphical abstract: Highlights: CdSe/SnO2 with feasible strategy was fabricated for enhanced OER and overall water splitting. Synergistic effect exhibited due to the superior active sites in the composite. It displaying the exceptional lower overpotential (233 mV) for OER, reaching at current density 10 mA/cm 2 with smaller Tafel slope (89 mV dec -1 ) It employed for overall water splitting in two electrode system with minute cell potential (2.4 V vs RHE). Abstract: Various electrocatalysts were employed to explore bottleneck oxygen evolution reaction (OER), a critical and essential reaction in metal ion batteries and water splitting for obtaining clean hydrogen fuel. Replacement of noble metals catalysts with non-noble metals is trending due to their specific characteristics such as eco-friendly, cheap, and electrocatalytic activity. Herein, we synthesized CdSe/SnO2 with a feasible strategy that is commercially favorable because of their non-expensive and ease of availability as well as their enhanced catalytic activity supporting overall water splitting. Several characterization techniques were performed to confirm and analyze the successful synthesis and activity of CdSe/SnO2 nanocomposite. The unique morphology of nanocomposite exhibits enhanced surface area, which increases active sites with abundant charge transfer potential and also supports the material for an extended period. Synergistic effect exhibited due to the superior active sites and the composite display an exceptional lower overpotential (233 mV) for OER, reaching at current density (j) of 10 mA cm −2 with smaller Tafel slope of 89 mV dec -1, showing high charge transfer during the OER representing good electrocatalytic performance on the graphite pencil electrode (GPE). The synthesized material is also used for overall water splitting with minute cell potential (2.4 V vs. RHE). The nanocomposite design by this strategy can also be used for many other materials to enhance the efficiency of the materials for future applications.